Ecoepidemiology of Chagas Disease in a Biological Corridor in Southeastern Mexico: A Promising Approach to Understand the Risk of Chagas Disease - Ingrid Yazmin Cruz-Alegría; Nancy Gabriela Santos-Hernández; Christian Ruiz-Castillejos; Juan Felipe Ruan-Soto; Adriana Moreno-Rodríguez; Any Laura Flores-Villegas; Javier Gutiérrez-Jiménez; Luis Arturo Hernández-Mijangos; Eduardo Estanislao Espinoza-Medinilla; Dolores Guadalupe Vidal-López; José Antonio De Fuentes-Vicente (Journal of Parasitology Research)
Ecoepidemiology is an emerging field that attempts to explain how biotic, environmental, and even social factors influence the dynamics of infectious diseases. Particularly in vector-borne diseases, the study under this approach offers us an overview of the pathogens, vectors, and hosts that coexist in a given region and their ecological determinants. As a result of this, risk predictions can be established in a changing environment and how it may impact human populations. This paper is aimed at evaluating some ecoepidemiological characteristics of Chagas disease in a natural reserve in southeastern Mexico that borders human settlements. We carry out a cross-sectional study in 2022 where we search insects manually and with light traps. We set traps for small mammals and bats and conducted interviews with the inhabitants living around the study site. We identified the presence of Triatoma dimidiata and T. huehuetenanguensis species with a percentage of TcI T. cruzi infection of 68.4% (95% CI: 66.9-69.9). Temperature and humidity were not determining factors for the probability of insect capture. Of the 108 wild mammals (Chiroptera, Rodentia, and Didelphimorphia), none was infected with T. cruzi. Knowledge about Chagas disease in nearby inhabitants is poor, and some characteristics were found on the periphery of dwellings that could offer a refuge for insect vectors. With this information, surveillance strategies can be generated in the study area that reduce the risk of transmission of T. cruzi parasite to humans, and it is expected to motivate the use of this field in future research.